Investment Through Mutual Fund - Chauhan, Sudhir Kumar; Gupta, Shalabh (Journal of Commerce and Trade, 2011)
Indian Mutual Fund Industry is increasing by leaps and bound . Since its inception in 1964 there was only 25 cr. Assets under management like a sapling but now it has grown into a big banyan tree with assets of Rs. 4,81,749 cr under assets management companies up to march 2010. It shows that people are investing through Mutual fund due to its low risk, uniqueness and special benefits. In the present research paper an endeavour is made to aware the investment community about the Mutual Fund schemes, its growth during the years and investment strategy to make extra ordinary return from the investment in various schemes of Mutual Fund operated by both public and private sector.